Georgios Nikolaou Papanikolaou - А. D. Kondrashova; K. N. Grigoreva (Акушерство, гинекология и репродукция, 2024)
Over entire life, Georgios Nikolaou Papanikolaou studied cytology of the female reproductive system. Owing to Dr. Papanikolaou’sefforts, the Pap test was created, which is relevant in diagnostics of early stage cervical cancer even today.